2009
DOI: 10.1007/s12033-009-9213-5
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Protein Expression in Leishmania tarentolae

Abstract: A variety of recombinant protein expression systems have been developed for heterologous genes in both prokaryotic and eukaryotic systems such as bacteria, yeast, mammals, insects, transgenic animals, and plants. Recently Leishmania tarentolae, a trypanosomatid protozoan parasite of the white-spotted wall gecko (Tarentola annularis), has been suggested as candidate for heterologous genes expression. Trypanosomatidae are rich in glycoproteins, which can account for more than 10% of total protein; the oligosacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 49 publications
1
68
0
2
Order By: Relevance
“…Collectively, the studies demonstrate that the basic features of the Trypanosomatidae secretory-endocytic pathways are very similar to those found in higher eukaryotic expression systems such as mammalian cell lines (Ralton et al 2002;Clayton and Shapira 2007;Basile and Peticca 2009). Hence, in this study an attempt was made to express the recombinant human IFN-c in L. tarentolae.…”
Section: Discussionmentioning
confidence: 64%
“…Collectively, the studies demonstrate that the basic features of the Trypanosomatidae secretory-endocytic pathways are very similar to those found in higher eukaryotic expression systems such as mammalian cell lines (Ralton et al 2002;Clayton and Shapira 2007;Basile and Peticca 2009). Hence, in this study an attempt was made to express the recombinant human IFN-c in L. tarentolae.…”
Section: Discussionmentioning
confidence: 64%
“…For example, Laminin (LM)-332, a large heterotrimeric glycoprotein, produced in L. tarentolae has shown similar cell adhesion activity to LM-332 which was purified from mammalian cells, indicating its proper folding and assembly [21]. Moreover, this system is suitable to express recombinant proteins with a tag, allowing easy purification and detection of the recombinant protein [22].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeting the activation of DCs is an important strategy associated with the development of cancer vaccines since these cells play a central role in the induction of anti-tumor immunity (Seo et al, 2009). In the present study, we investigated the potential of a non-pathogenic parasite, L. tarentolae (Basile & Peticca, 2009) against tumor as a live vaccine candidate vector to efficiently target DCs and lymphoid organs, thus enhancing antigen presentation and consequently influencing the magnitude and quality of T cell immune responses. In addition, the fusion of antigen with heat shock proteins is one such strategy for enhancing immune responses and regression of HPV-16 E7-expressing tumors in mice (Devaraj et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an urgent need for the development of new safe live vaccine vectors that are capable of enhancing antigen presentation and eliciting potent immune responses without the risk of development of disease in humans. Recently, Leishmania tarentolae (L.tar), a unicellular eukaryotic protozoan, has been established as candidate for heterologous genes expression (Basile & Peticca, 2009). The studies have shown the potential of L. tarentolae that is non-pathogenic to humans, as a live candidate vaccine.…”
Section: Introductionmentioning
confidence: 99%